2021
DOI: 10.1002/bin.1789
|View full text |Cite
|
Sign up to set email alerts
|

The Social Referencing Observation Scale (SoROS) for children: Scale development and reliability

Abstract: The Social Referencing Observational Scale (SoROS) is being developed to measure and detect deficits in social referencing skills in children between 2.6 and 5.0 years of age. This study is the first in the sequence, describing the first phases of development. First, three different scenarios designed to evoke social referencing behaviors were selected. We called the scenarios Fear, Pain, and Joy. In the pilot study, social referencing in 60 typical children was scored. Based on the data from the pilot study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The SoROS is a systematic behavioral assessment, based on direct observations during three scenarios, where the child observes three emotional expressions (i.e., fear, pain, and joy) presented by the administrator. The three scenarios are a continuation of Sigman's (1988) In a previous study, we assessed TD children aged between 2.6 and 5 years (Lubomirska et al, 2021). We found that the behaviors most frequently exhibited by TD children were looking at the administrator when the administrator expressed fear, pain, or joy, and, subsequently, taking some action with the materials.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…The SoROS is a systematic behavioral assessment, based on direct observations during three scenarios, where the child observes three emotional expressions (i.e., fear, pain, and joy) presented by the administrator. The three scenarios are a continuation of Sigman's (1988) In a previous study, we assessed TD children aged between 2.6 and 5 years (Lubomirska et al, 2021). We found that the behaviors most frequently exhibited by TD children were looking at the administrator when the administrator expressed fear, pain, or joy, and, subsequently, taking some action with the materials.…”
Section: Introductionmentioning
confidence: 95%
“…In a previous study, we assessed TD children aged between 2.6 and 5 years (Lubomirska et al., 2021). We found that the behaviors most frequently exhibited by TD children were looking at the administrator when the administrator expressed fear, pain, or joy, and, subsequently, taking some action with the materials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations